Analisis Wacana Kritis Teks Berita Kampus Pada Media Online Sketsaunmul.Co: Model Theo Van Leeuwen - Laily, Asyifa Ismatul; Mulawarman, Widyatmike; Putri, Nina Queena Hadi (Adjektiva: Educational Languages and Literature Studies, 2020)
This study is focused on the social actors (individual or group) who are described by the writers in the news. The type of research used is a qualitative approach with descriptive presentation of the results. The data were collected by using observation, documentation and writing method. The data analysis technique used is the discourse of Theo Van Leeuwen model with the stages of data analysis are data collection, data reduction, data presentation, and conclusion drawing. The data in this research is the sentences of the news which contain Theo Van Leeuwen model discourse theory. The data resource of this study is from an online media, Sketsaunmul.co website, specifically released from November to December 2019 with 36 news total. After analyzing data, the result of Critical Discourse Analysis of Campus News Texts on Online Media Sketsaunmul.co: A Theo Van Leeuwen Model study was found. The writers try to show or cite clearly the social actors who is involved in an certain event, so found inclusion strategic (entry process) the social actors in the news text. Then, every data in the sentence form would be explained by each strategic inclusion category according to Theo Van Leeuwen theory.